Long noncoding RNA SMUL suppresses SMURF2 production-mediated muscle atrophy via nonsense-mediated mRNA decay - Bolin Cai; Zhenhui Li; Manting Ma; Jing Zhang; Shaofen Kong; Bahareldin Ali Abdalla; Haiping Xu; Endashaw Jebessa; Xiquan Zhang; Raman Akinyanju Lawal; Qinghua Nie (Elsevier, 2021)
As the world population grows, muscle atrophy leading to muscle wasting could become a bigger risk. Long noncoding RNAs (lncRNAs) are known to play important roles in muscle growth and muscle atrophy. Meanwhile, it has recently come to light that many putative small open reading frames (sORFs) are hidden in lncRNAs; however, their translational capabilities and functions remain unclear. In this study, we uncovered 104 myogenic-associated lncRNAs translated, in at least a small peptide, by integrated transcriptome and proteomic analyses. Furthermore, an upstream ORF (uORF) regulatory network was constructed, and a novel muscle atrophy-associated lncRNA named SMUL (Smad ubiquitin regulatory factor 2 [SMURF2] upstream lncRNA) was identified. SMUL was highly expressed in skeletal muscle, and its expression level was downregulated during myoblast differentiation. SMUL promoted myoblast proliferation and suppressed differentiation in vitro. In vivo, SMUL induced skeletal muscle atrophy and promoted a switch from slow-twitch to fast-twitch fibers. In the meantime, translation of the SMUL sORF disrupted the stability of SMURF2 mRNA. Mechanistically, SMUL restrained SMURF2 production via nonsense-mediated mRNA decay (NMD), participating in the regulation of the transforming growth factor β (TGF-β)/SMAD pathway and further regulating myogenesis and muscle atrophy. Taken together, these results suggest that SMUL could be a novel therapeutic target for muscle atrophy.